2000
DOI: 10.1037/0022-3514.78.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Studying the dynamics of emotional expression using synthesized facial muscle movements.

Abstract: Synthetic images of facial expression were used to assess whether judges can correctly recognize emotions exclusively on the basis of configurations of facial muscle movements. A first study showed that static, synthetic images modeled after a series of photographs that are widely used in facial expression research yielded recognition rates and confusion patterns comparable to posed photos. In a second study, animated synthetic images were used to examine whether schematic facial expressions consisting entirel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
205
3
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(238 citation statements)
references
References 36 publications
(64 reference statements)
16
205
3
6
Order By: Relevance
“…Respondents were exposed to 5-s moving pictures showing a male model producing dynamic angry or happy facial expressions. We used dynamic presentations because moving images of facial expressions may constitute a stronger eliciting stimulus than static displays (Wehrle et al, 2000). Facial EMG activity in the zygomaticus major and corrugator supercilii muscle regions was assessed during exposure to the facial stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Respondents were exposed to 5-s moving pictures showing a male model producing dynamic angry or happy facial expressions. We used dynamic presentations because moving images of facial expressions may constitute a stronger eliciting stimulus than static displays (Wehrle et al, 2000). Facial EMG activity in the zygomaticus major and corrugator supercilii muscle regions was assessed during exposure to the facial stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Motion of emotional expressions, in addition to shape information, presents a rich display of emotional state. In fact, Wehrle, Kaiser, Schmidt, and Scherer [35] provide evidence that the addition of dynamic information improves emotional processing. However, we expected that emotion recognition skills of dynamic distress signals would be impaired for youth high in CU traits even with the added motion information.…”
mentioning
confidence: 99%
“…Research has shown that humans are quite adept at identifying emotions in static line drawings [Wehrle, Kaiser, Schmidt, & Scherer 2000] and remarkably proficient at gleaning critical information from even the most impoverished dynamic displays [Barclay, Cutting, & Kozlowski 1978]. Thus, even a low fidelity simulation can result in positive training benefits, provided that the critical cues are present and the key behaviors are exercised.…”
Section: Introductionmentioning
confidence: 99%